Structural Racism as an Ecosystem: An Exploratory Study on How Structural Racism Influences Chronic Disease and Health and Wellbeing of First Nations in Canada - Krista Stelkia (International Journal of Environmental Research and Public Health, 2023)
Indigenous peoples in Canada experience disproportionately higher rates of chronic disease than their non-Indigenous counterparts. Previous research has identified structural racism as a powerful determinant of health and wellbeing. Mounting evidence demonstrates that First Nations are disproportionately over-represented, compared to other Canadians, in several domains that have been used to measure structural racism in other countries. Despite growing concern of the impact of structural racism on health, there remains little empirical evidence on the impact structural racism has on chronic disease health outcomes of First Nations. This qualitative study examines the complex and intersecting ways in which structural racism can influence chronic disease health outcomes and the overall health and wellbeing of First Nations in Canada. In-depth semi-structured interviews were conducted with twenty-five participants, including subject matter experts in health, justice, education, child welfare, politics, and researchers in racism scholarship and First Nations who have lived experience with a chronic condition(s). Thematic analysis was used to analyze the data collected. Six themes on how structural racism influences chronic disease and the health of First Nations were identified: (1) multiple and intersecting pathways; (2) systems of failure, harm, and indifference; (3) impacts on access to healthcare; (4) colonial policies of structural deprivation; (5) increased risk factors for chronic disease and poor health; and (6) structural burden leading to individual-level outcomes. Structural racism creates an ecosystem that negatively impacts chronic diseases and the health of First Nations. The findings illuminate how structural racism can have micro-level influences at an individual level and can influence one’s chronic disease journey and progression. Recognizing how structural racism shapes our environments may help to catalyze a shift in our collective understanding of the impact of structural racism on health.